Impact of microneedling on reducing perioral wrinkles - Fariba Iraji; Amir Hossein Siadat; Fatemeh Mokhtari; Mohsen Hosseini; Maryam Fatahinasab (مجله علوم پزشکی فیض (پیوسته))
Background and Aim: Skin aging is a natural process, and microneedling is a method used for skin rejuvenation. This study aimed to evaluate the impact of microneedling on reducing perioral wrinkles. Methods: A clinical trial was conducted on 30 women referred to a skin clinic in Isfahan, Iran, from December 22, 2021, to June 20, 2022. The patients underwent three microneedling sessions at 2-week intervals. Perioral wrinkles were photographed using a digital camera under consistent conditions and at a distance of 30 cm before the intervention, 6 weeks post-intervention, and 3 months after the final treatment session. Two dermatologists, blinded to the treatment, assessed the photographs. Moreover, patients self-reported improvement using the Visual Analog Scale (VAS) at the beginning, 6 weeks, and 3 months after the intervention. Results: Following the microneedling sessions, the first dermatologist reported poor improvement in 7 (23.3%), moderate improvement in 14 (46.7%), good improvement in 7 (23.3%), and excellent improvement in 2 (6.7%) cases. The second dermatologist observed good improvement in 13 (43.3%), moderate in 11 (36.7%), and poor improvement in 6 (20%) patients. According to patient reports, perioral wrinkles showed significant improvement at 6 weeks and 3 months post-intervention compared to baseline (P<0.001). Additionally, there was a significant improvement in perioral wrinkles at 3 months compared to 6 weeks post-intervention (P<0.001). Conclusion: The results suggest that three microneedling sessions at 2-week intervals led to a significant improvement in perioral wrinkles based on assessments by dermatologists and patient reports.